Bridging the Gap Between Research and Practice: Using Creative Methods to Research Transactional Analysis Psychotherapy. (3rd April 2022) - Haynes, Emma
Abstract: Research using creative methods is opening up new ways to deepen our understanding of human experience and offer possibilities to all fields of transactional analysis (TA). This paper shows how creative methods can enrich both transactional analysis research and practice, particularly with reference to unconscious processes and silence. The author provides a brief overview of two types of creative method followed by some of the results obtained from using them in a TA research project. A case vignette is used to illustrate how one of these methods was applied in practice in the hope of showing how creative methods can be useful tools for offering transactional analysis a possible bridge into what Christopher Bollas described as "the unthought known."